Development of a Website for Disseminating Knowledge About listening Effort for Professionals - de Miranda Cantuaria Alves, Heloisa; de Oliveira, Jerusa Roberta Massola; do Amaral, Sandra Lia [UNESP]; Valenti, Vitor Engrácia [UNESP]; Mondelli, Maria Fernanda Capoani Garcia (Thieme, 2024)
Introduction Permanent education in health aims to ensure that professionals are constantly learning in the workplace and in the last few years institutions resorted to the technology-mediated education modality and new teaching possibilities were explored. In Brazil, between 2017 and 2021, only six articles and five monographs were published about listening effort. Objective The objective of this study was to develop a website with scientific content on the topic listening effort for Speech -Language Therapist and Audiologist with free online access. Methods The study was carried out in five stages: Analysis, contemplating the search for scientific materials to prepare the material. Design, in which the writing and design of the website was carried out. Development, carrying out the adequacy of the online material. Implementation, a stage in which professionals in the area evaluated the quality of the material after consenting to participation through a free and informed consent term. Review, stage in which the researcher analyzed the evaluators' responses. Results The five stages of elaboration of the website were carried out, which was evaluated by professionals in the area. The average of responses to all applied questions rated the website as superior. Conclusion The website development was validated for online availability.
Keywords: audiology; educational technology; health education; listening effort